Religion Affects Future Female Doctors' Approach to HPV Vaccination in Czech and Slovak Republics - Zahumensky, Jozef; Psenkova, Petra; Melnikova, Livia; Drabiscakova, Paula; Nadzamova, Alexandra; Kacerovsky, Marian; Simetka, Ondrej; Dosedla, Erik (Journal of cancer education, 2021)
The objective of this study is to summarize the factors, including religion, affecting an individual's decision to get vaccinated or reject vaccination. Anonymous questionnaire-based electronic study is conducted in all faculties of medicine in Czech and Slovak republics. One thousand four hundred and six (1406) questionnaires were analyzed. Responders not practicing any religion received vaccination more often and would recommend vaccination more often. Catholic religion was the most important demographic factor affecting the rate of vaccination. In the group of Catholic female students, 21.9% were vaccinated. In the group of non-Catholic female students, 55.5% were vaccinated. In conclusion, female medical students' approach to vaccination depends, among other factors, on their individual beliefs.
Keywords: Religion; Surveys and Questionnaires; HPV vaccination; vakcíny proti papilomavirům; vakcinace; Humans; Vaccination; Anti-vaccination movement; studenti lékařství; Female; zdraví - znalosti, postoje, praxe; lidé; Slovakia; Slovenská republika; průzkumy a dotazníky; náboženství; Papillomavirus Infections; ženské pohlaví; Medical students; Czech Republic; Students, Medical; The Slovak and Czech republics; infekce papilomavirem; Health Knowledge, Attitudes, Practice; Papillomavirus Vaccines; Česká republika